ANALISIS KESALAHAN BERBAHASA PADA UNGGAHAN STATUS MEDIA SOSIAL FACEBOOK - Ray, Sukma Adelina; Yulianda, Asri; Mitha Monica, Sella; Muyassarah, Muyassarah (Jurnal Bahastra, 2024)
The focus in this study is language on Facebook social media, especially those concerning grammar and spelling that can affect the understanding and interpretation of messages by readers. Facebook social media has become one of the most popular communication platforms among the public.  This research refers to Andika Suphryadi's Facebook account status posts and comments uploaded from 2021-2022. This type of research is a qualitative description research that aims to describe in detail in the form of data collected in language research, namely in the form of words instead of numbers. Language errors in this study in Facebook status uploads concluded that errors found in Facebook social media accounts were 12 data, including 6 phoneme omission errors, 3 phoneme usage errors, 2 capital letter errors. Hence, the importance of communicating correctly and appropriately in social media. As social media users, we should always strive to improve language skills and double-check uploads before they are posted to avoid unnecessary mistakes.